Toward a Critical Understanding of the World/Global City Paradigm - Ravi Ghadge (Journal of Public and Professional Sociology)
In the last few decades, “the city” has emerged as an important entity in our understanding of contemporary globalization, both as a place and as a discourse. As a place, it has become critical in shaping the contours of the world economy leading to a renewed importance of “global cities.” The city (“world/global city”) has also become an important site of discourse. The “world/global city paradigm” has not only become a hegemonic academic discourse, but also a critical policy tool that directs and justifies restructuring of urban space in the global South. Through a synthesis of recent literature on urbanism in the US and the global South, this paper attempts to critically understand the “world/global city paradigm” and its rise within particular socio-historical contexts in the global North. Further, the paper examines the “paradigm’s” effectiveness in understanding urbanism in the South. The paper argues that given the specific contexts within which these urban discourses emerge, they are unable to critically address unique geometries of power and inequality and how they shape urbanism in the South. The paper concludes by offering some alternatives for a culturally and historically rooted analysis of urbanism.